Contents of Urinary System Stones in North Marmara Region and Their Distribution by Gender - Ekrem Güner; Kamil Gökhan Şeker (Journal of Urological Surgery, 2020)

(untitled)
Objective:We aimed to determine the contents of kidney stones in our country by evaluating the results of the stone analysis of patients who underwent surgery due to ureteral or kidney stones or experienced spontaneous stone expulsion.Materials and Methods:Data of patients with urolithiasis who underwent surgery due to ureteral or kidney stones or experienced spontaneous stone expulsion in our clinic between 1999 and 2019 were retrospectively analyzed.Results:Results of 1304 urinary system stone analyses were obtained. 869 (66.6%) patients were male and 435 (33.4%) were female. The male-to-female ratio was 1.99:1. The mean age of the patients was 43.2±15.3 years. Among 1304 urinary system stones, 734 (56.3%) had a single component, while 570 (43.7%) contained more than one substance. The most common stone type was calcium oxalate monohydrate (43%) and the second most common stone type was the composition of calcium oxalate monohydrate and calcium oxalate dihydrate (21.3%). The rate of uric acid stone was 6.8% and the rate of cystine stone was 2.1%. Any amount of calcium oxalate, uric acid and cystine were observed in 85.3%, 12.2% and 5.4% of urinary tract stones, respectively.Conclusion:Urinary system stone disease is approximately two times more frequent in men than in women in Turkiye and the most common stone component is calcium oxalate.